Respuesta :

eliminate y's
multiply second equaiton by 4
4x+4y=-4

add to first equation

3x-4y=-24
4x+4y=-4 +
7x+0y=-28

7x=-28
divide both sides by 7
x=-4
sub back

x+y=-1
-4+y=-1
add 4 to both sides
y=3

(x,y)
(-4,3)
D is answer
Good morning Stacy

3x - 4y = -24
x + y = -1
We need to solve x + y = -1 for x
x = -1 - y( I transferred the y in the right side)
Substitute -y -1 for x in 3x -4y = -24
3x - 4y = -24
3(-y-1) -4y = -24
You just need to simplify
-7y -3 = -24
-7y = -24 + 3
-7y = -21
y= -21/-7
y= 3
Now substitute 3 for y in x= -y -1
x= -y-1
x = -3 -1
x= -4

Answer : x = -4 and y=3
The correct option is D

I hope that's help and if you have questions about my answer please ask. Thx